Biospeckle Optical Coherence Tomography in Visualizing the Heat Response of Skin: Age-Related Differences - Ryosuke Nakasako; Jun Yamada; Takahiro Kono; Hirofumi Kadono; Uma Maheswari Rajagopalan (Applied Sciences)
Currently, research related to the visualization of cutaneous vascular changes to heat stress depending on age and gender is limited to methods such as laser Doppler flowmetry and plethysmography, which do not provide any spatially resolved information at high resolution. On the other hand, optical coherence tomography is a real-time, noninvasive, non-contact technique that can visualize internal structures at the level of a few microns and is widely used in ophthalmology to visualize retinal structures, for example. However, the use of OCT in the investigation of skin vasculature heat stress is limited, with no study being conducted with different genders and different age groups. In this study, we propose biospeckle optical coherence tomography (bOCT), which visualizes the structural changes along a temporal scale to visualize the dynamic changes within the skin under heat stress. Heat stress was applied by applying a USB hot pad (40 °C) for five minutes to the palmar forearm of the dominant hand. A swept-source OCT (SS-OCT) operating with a central wavelength of 1310 nm, a bandwidth of 125 nm, and a sweep frequency of 20 kHz was used to obtain OCT structural images at 12.5 fps. From the one hundred OCT structural images recorded for 8 s, the biospeckle image was calculated as a ratio of the standard deviation to the mean of the images. The biospeckle images were obtained before heating, soon after heating, and after 5 min of rest. A total of 20 subjects with an equal number of male and female participants, with 10 in their 20s and the other 10 in their 30s or older, participated in the experiments. The average biospeckle contrast results were compared for significant differences under the three different conditions of before heating, soon after heating, and after rest for different depths, age differences, and genders. With heating, across all subjects at shallow depths within 200 µm or so, possibly in the epidermis–dermis border region, a significant difference was observed in the average contrast between the before-heating and after-rest conditions, with no significant difference seen in the deeper regions. With respect to age groups irrespective of gender, there was only a significant difference in the average contrast between soon after heating and before heating for the younger group, while for the older group, there was significant difference between before heating and soon after heating as well as between before heating and after 5 min of rest. This result suggests that age plays a larger role in the control of vascular dynamics. With respect to gender and irrespective of age, there was significant difference between males and females for both soon after heating and after 5 min of rest, with no significant difference found for before heating. These differences could be explained by hormonal differences that play a larger role in the vascular dynamics of the control of skin under heat stress, though the clear mechanism behind the reason for these gender differences is not clearly understood yet. As for both gender and age, because of the smaller sample size for age and gender combined, more studies are needed to obtain statistically reliable results. In total, our results obtained using bOCT demonstrate that bOCT could be successfully implemented in the study of the environmental effects on skin tissue, and we believe this has potential implications in therapeutic use such warm water immersion.